Ambient air pollution and racial/ethnic differences in carotid intima-media thickness in the Multi-Ethnic Study of Atherosclerosis (MESA). Issue 12 (3rd July 2015) - Jones, Miranda R; Diez-Roux, Ana V; O'Neill, Marie S; Guallar, Eliseo; Sharrett, A Richey; Post, Wendy; Kaufman, Joel D; Navas-Acien, Ana
Abstract : Background: In the USA, ethnic disparities in atherosclerosis persist after accounting for known risk factors. Ambient air pollution is associated with increased levels of atherosclerosis and differs in the USA by race/ethnicity. We estimated the influence of ambient air pollution exposure to ethnic differences in common carotid intima-media thickness (IMT). Methods: We cross-sectionally studied 6347 Caucasian-American, African-American, Hispanic and Chinese adults across 6 US cities in 2000–2002. Annual ambient air pollution concentrations (fine particulate matter [PM2.5 ] and oxides of nitrogen [NOX ]) were estimated at each participant's residence. IMT was assessed by ultrasound. Results: The mean IMT was 19.4 and 37.6 μm smaller for Hispanic women and men, 53.6 and 7.1 μm smaller for Chinese women and men, and 23.4 and 38.7 μm higher for African-American women and men compared with Caucasian-American women and men. After adjustment for PM2.5, the differences in IMT remained similar for Hispanic and African-American participants but was even more negative for Chinese participants (mean IMT difference of −58.4 μm for women and −15.7 μm for men) compared with Caucasian-American participants. The IMT difference in Chinese participants compared with Caucasian-American participants related to their higher PM2.5 exposures was 4.8 μm (95% CI 0.2 to 10.8) for women and 8.6 μm (95% CI 3.4 to 15.3) for men. NOX was not related to ethnic differences in IMT. Conclusions: The smaller carotid IMT levels in Chinese participants were even smaller after accounting for higher PM2.5 concentrations in Chinese participants compared with Caucasian-American participants. Air pollution was not related to IMT differences in African-American and Hispanic participants compared with Caucasian-American participants.